Design and Synthesis of Two Brucine Derivatives and Evaluation of Its Antibacterial Activity Against Escherichia coli and Salmonella typhi - Figueroa-Valverde, Lauro; Diaz-Cedillo, Francisco; Lopez-Ramos, Maria; Garcia-Cervera, Elodia; Pool-Gomez, Eduardo (Asian Journal of Chemistry, 2012)
In this study two brucine derivatives were synthesized. The first step was achieved by the reaction of brucine with ethylenediamine using boric acid as catalyst to form an imine group (Schiff base) involved in the compound 3. The second step involves the coupling of ethylenediamine to brucine by the method reported by Mannich, using formaldehyde to form the compound 4. The antibacterial activity of both brucine derivatives was evaluated in vitro on Escherichia coli and Salmonella typhi using the dilution method and the minimum inhibitory concentration. The results showed that bacterial growth of Escherichia coli was inhibited by the compounds 3 and 4 in a dose-dependent manner. Nevertheless, the bacterial growth of Salmonella typhi only was blocked by the compound 3. These data suggest that functional groups involved in the structure of 3 are specific for its antibacterial activity.